Integration of risk and uncertainty on levelized cost of electricity calculation - Cunha, Jorge (2019)
The electric sector is still largely dependent on non-renewable energy sources. The importance of using renewable energies is increasingly recognized all across the world yet they are not fully ready to compete with the mature and ancient technologies that use non-renewable energies. The economic characteristics of different energy technologies can be compared by using the method of levelized cost of electricity (LCOE). LCOE represents the total cost of a power plant including investment and operation and maintenance costs over the assumed life-cycle and discounted to account for the time-value of money. In this paper, an analysis of the levelized costs is proposed for two renewable technologies in Portugal: wind power and solar photovoltaic. Firstly, a deterministic value of LCOE was computed for both technologies. Secondly, recognizing the uncertainty associated with all the assumed parameters, a probabilistic risk analysis was conducted with Monte Carlo simulation to complement the analysis. The results show the high variability of the obtained LCOE values, largely influenced by the investment values and load factors.